Influence of concave-convex dies on bending damage of multilayer metal plate - SHANG JinPing; LI Jing; YI Fei (Jixie qiangdu)
The concave-convex die plays an important role in the metal plate bending process, and the fillet radius of the concave-convex die is a key parameter in the design of the bending process. Due to the delamination damage of the single-layer metal plate during the bending process of the multilayer metal plate, this paper mainly studied the influence of the concave-convex die on the damage of the multilayer metal plate during the bending process, and the test was carried out by changing the corresponding die parameters and verified by finite element simulation. The results show that delamination damage occurs in the bending process of the multi layer metal plate. Without changing the punch, the degree of delamination damage will gradually decrease with the increase of the fillet radius of the die, and the bending effect of the multilayer metal plate is better. At the same time, it is found that when the fillet radius of the concave die is equal to the sum of the fillet radius of the punch and the thickness of the metal plate, the bending performance of the multilayer metal plate is the best, and there is basically no delamination damage.